Electrochemotherapy with intravenous bleomycin for heavily pre-treated vulvar cancer patients. Issue 4 (14th February 2023) - Perrone, Anna Myriam; Corrado, Giacomo; Coada, Camelia Alexandra; Garganese, Giorgia; Fragomeni, Simona Maria; Tagliaferri, Luca; Di Costanzo, Stella; De Crescenzo, Eugenia; Morganti, Alessio Giuseppe; Ferioli, Martina; De Terlizzi, Francesca; Scambia, Giovanni; et al.
Abstract : Objective: The management of vulvar cancer recurrences is complicated by patients' advanced age and comorbidities. Bleomycin-based electrochemotherapy is a potential treatment option in this setting. However, no data on long-term outcomes are available. Therefore, a multicenter observational study was designed to evaluate the 5-year results in these patients. Methods: Data about patients and tumor characteristics, electrochemotherapy cycles, clinical response, and follow-up were recorded. Treatment procedures were performed according to the European Standard Operating Procedures of Electrochemotherapy (ESOPE) guidelines. Response was evaluated according to the Response Evaluation Criteria in Solid Tumors (RECIST) criteria. Results: Fifty-one patients (mean age 82.31±7.28 years) with squamous cell vulvar cancer underwent electrochemotherapy (median number of sessions 1; range 1–4). 20 patients had complete response and 32% of these were disease-free after 2 years (median progression-free survival 16.8 months). In 13 patients with partial response the median progression-free survival was 15.36 months, while patients with stable or progressive disease showed tumor relapse after 6.95 and 3.26 months, respectively (p<0.001). Median overall survival was 18.77, 13.07, 6.73, and 11.13 months in patients with complete response, partial response, stable disease, and progressive disease, respectively (p=0.001). Conclusion: Long-term follow-up of vulvar cancer patients showed reasonable tumor control after electrochemotherapy and improved progression-free survival and overall survival in responder subjects compared with non-responders. Further studies aimed at improving local response after electrochemotherapy are warranted. Thus, this approach represents a potential alternative for these patients.